Двухконтинуумная механика диэлектриков как основа теории пьезоэлектричества и электрострикции - Хорошун, Л.П. (Прикладная механика, 2018)
Изложенный новый принцип построения теории линейной и нелинейной электроупругости, в основу которого положены уравнения двухконтинуумной механики диэлектриков как смеси положительных и отрицательных зарядов, попарно связанных в нейтральные молекулы или ячейки, позволяет устранить отмеченные недостатки. Викладено новий принцип побудови теорії зв’язаних динамічних процесів електропружності діелектриків, яким властиві п’єзоефект і електрострикція. В основу теорії покладено чисто механічні уявлення про двохконтинуумний опис деформування діелектрика як суміші попарно зв’язаних у нейтральні молекули чи елементарні комірки позитивних і негативних зарядів при умові існування пружного потенціала і лінійно-квадратичної залежності парціальних напружень від різниці переміщень зарядів. Виходячи з визначення вектора поляризації елементарного макрооб’єму діелектрика і породжуваного ним електричного поля, рівняння двохконтинумної механіки перетворюються у зв’язані динамічні рівняння відносно макропереміщень нейтральних молекул і напруженостей електричного поля, які описують п’єзоелектричні і електрострикційні ефекти. A new principle is expounded for constructing the theory of coupled dynamical processes of electroelasticity of dielectrics that have the properties of piezoeffect and electrostriction. This theory is based on the purely mechanical view on the two-continuum description of deformation of dielectrics. The dielectrics are thought as a mixture of positive and negative charges which are linked in pairs into the neutral molecules or elementary cells. At that, the condition of existence of the elastic potential and linear - quadratic dependence of partial stresses on the difference of displacements of charges is accepted. Starting with the definition of polarization vector of elementary macrovolume and generated by its electric field, the equations of two-continuum mechanics are transformed into the coupled dynamic equations for the microdisplacements of neutral molecules and electric-field strength that describe the piezoelectric and electrostriction effects. The Maxwell’s equations follow from these equations as a particular case.